FACTORS DETERMINING BUYER-SELLER RELATIONSHIPS: EMPIRICAL RESULTS FROM AN AGRIBUSINESS PERSPECTIVE - Hesty Nurul Utami; Dini Turipanam Alamanda; Risma Muhamad Ramdani (Universitas Padjadjaran, 2022)
Continuous development of the Indonesian agri-food retail in the past decades has shown an evolutionary way on how the buyer and seller build their interaction during the exchange transaction process. It shows the significance of beneficial buyer-seller relationships in the shifting from traditional food retailing model to modern food retailing model, including in developing economy context. The study aims to investigate the factors affecting the buyer-seller relationship concept to access the modern market from the farmer producer perspective in the setting of an emerging market. This study surveyed 75 respondents of vegetable farmer group members located in a vegetable cluster in West Java, Indonesia. An explanatory quantitative method with Confirmatory Factor Analysis (CFA)was used for the data analysis. The findings verified four primary factors that can explain the B2B buyer-seller relationship of farmers deciding to partner with modern retailers such as supermarkets, which consists of trust, loyalty, relationship commitment, and business communication. The findings propose a further understanding related to the factors that influence the buyer-seller inter-relationships in the B2B context of the agriculture sector.